PERGANTIAN AUDITOR SEBAGAI UPAYA MENJAGA INDEPENDENSI - Djuharni, Darti; Fathonah, Annisa Dini; Sonhaji, Sonhaji (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. This study aims to examine and analyzeg factors related to auditor replacement.Research Method. The unit of analysis in this study is all property and real estate sector companies listed on the Indonesia Stock Exchange, and 23 companies are taken as samples that meet the criteria, the total number observed is 92 in the form of annual reports for the 2016-2019 period. Data were analyzed using logistic regression analysis.Research Result and Findings. The results of this study reveal that management turnover and audit fees have no effect on auditor switching, while audit delay affects auditor switching. The results of this research are expected to be a consideration for companies in making decisions for auditor replacement.